Pharmacologic options for the treatment and management of food allergy. Issue 5 (September 2015) - Kobernick, Aaron K; Chambliss, Jeffrey; Burks, A Wesley
<x xml:space="preserve">Abstract</x> Food allergy affects approximately 5% of adults and 8% of children in developed countries, and there is currently no cure. Current pharmacologic management is limited to using intramuscular epinephrine or oral antihistamines in response to food allergen exposure. Recent trials have examined the efficacy and safety of subcutaneous, oral, sublingual, and epicutaneous immunotherapy, with varying levels of efficacy and safety demonstrated. Bacterial adjuvants, use of anti-IgE monoclonal antibodies, and Chinese herbal formulations represent exciting potential for development of future pharmacotherapeutic agents. Ultimately, immunotherapy may be a viable option for patients with food allergy, although efficacy and safety are likely to be less than ideal.